A Case Report of Familial Extramammary Paget's Disease in Female Siblings - Thanachat Rutnumnoi (2022)
Extramammary Paget's disease (EMPD) is a rare intraepithelial neoplasm that occurs in apocrine-bearing areas of skin. Most EMPD patients initially present with chronic pruritic eczematous lesions involving genitalia, perineum and perianal area. Familial form of EMPD is extremely rare. Several genetic mutations have been proposed but specific modes of inheritance are still unknown. This article reports two cases of familial extramammary Paget's disease in female siblings.